2022
DOI: 10.1039/d2sc04630j
|View full text |Cite
|
Sign up to set email alerts
|

The three-center two-positron bond

Abstract: Computational studies have shown that one or more positrons can stabilize two repelling atomic anions through the formation of two-center positronic bonds. In the present work, we study the energetic...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
3
0
1
Order By: Relevance
“…22 It seems reasonable to assume that its dual in the lithium diatomic series is the Li 2 − anion and an MC-QTAIM analysis may help to uncover the nature of bonding in this species. The three-center two-positron bonds are also worth considering in detail since, as emphasized by Reyes and coworkers, 49 these are linked to fundamental chemical concepts like σ-aromaticity/anti-aromaticity and pseudo-metallic character. In fact, the unequivocal discovery of any form of anti-matter aromaticity may extend the concept beyond purely electronic matter, which in itself is an intriguing possibility.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 It seems reasonable to assume that its dual in the lithium diatomic series is the Li 2 − anion and an MC-QTAIM analysis may help to uncover the nature of bonding in this species. The three-center two-positron bonds are also worth considering in detail since, as emphasized by Reyes and coworkers, 49 these are linked to fundamental chemical concepts like σ-aromaticity/anti-aromaticity and pseudo-metallic character. In fact, the unequivocal discovery of any form of anti-matter aromaticity may extend the concept beyond purely electronic matter, which in itself is an intriguing possibility.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…22 Reyes and coworkers also proposed the first example of a multi-center two-positron bond through a detailed study of 2e + [H 3 3− ], which is a system composed of three hydride ions arranged in an equilateral triangle equilibrium geometry. 49 They did a detailed comparative study with H 3 + and Li 3 + , as representatives of the two-electron three-center bonds. Their analysis revealed that 2e + [H 3 3− ] indeed possess a two-positron three-center bond but from a quantitative viewpoint, it was demonstrated that 2e + [H 3 3− ] is much more similar to Li 3 + than H 3 + .…”
Section: Introductionmentioning
confidence: 99%
“…the molecule would dissociate into H 2 and Ps 2 . Charry et al 9 showed that a distinct nonelectronic three-centre, two positron bond could be formed in a system containing two positrons and three hydride ions.…”
Section: Introductionmentioning
confidence: 99%
“…Por meio da metodologia APMO, foi possível prever a existência de novas espécies positrônicas, especificamente a formação de ligações covalentes positrônicas entre dois ânions atômicos [36,37], possibilidade corroborada por estudos subsequentes [38][39][40]. Essas previsões motivaram novos estudos computacionais, que apontaram a estabilidade de moléculas positrônicas ainda mais complexas, nas quais mais de um pósitron está envolvido na ligação [41][42][43]. Esta Tese investiga moléculas positrônicas neutras, formadas pela adição de átomos de Ps a moléculas neutras, motivada tanto por experimentos recentes quanto pela ambição de propor novos experimentos.…”
Section: Lista De Tabelasunclassified